A Missouri author in a Roman law court: Pudd'nhead Wilson as an allegory of colourblind empire. Issue 2 (3rd July 2017) - Stabler, Albert
ABSTRACT: In his novel Pudd'nhead Wilson, set in the later antebellum period but written after Reconstruction, Mark Twain dramatizes the contradictions of the American racial hierarchy. In the story a light-skinned young man, born a slave but switched in the cradle with a free child, meets a tragic fate when his identity is revealed. The novel forms an unintentional bridge between the ancient Roman law of slavery, the foundation of much American slave law, and America's contemporary 'colourblind' legal consensus, which coexists with a historically unprecedented, racially distorted system of mass incarceration. In ancient Rome, unlike the antebellum US, slaves carried no indelible visual markers of their status, and many were eventually freed. These conditions led to a great deal of legislation and litigation around status confusion, the legal matter at the heart of Pudd'nhead Wilson . A new form of status confusion exists in the US after emancipation; none are formally designated as slaves under the law, and race-based laws have supposedly been eliminated, and yet the law punishes the descendants of slaves en masse, in proportion to their pigmentation. This paper considers and compares these three circumstances of status confusion, toward the end of reasserting the central importance of race in the contemporary legal environment, and in white Americans' civic fantasies.